Online educational research with middle adolescent populations: Ethical considerations and recommendations. (April 2021) - Mackenzie, Erin; Berger, Nathan; Holmes, Kathryn; Walker, Michelle
Adolescent populations have become increasingly accessible through online data collection methods. Online surveys are advantageous in recruiting adolescent participants and can be designed for adolescents to provide informed consent without the requirement of parental consent. This study sampled 338 Australian adolescents to participate in a low risk online survey on adolescents' experiences and perceptions of their learning in science classes, without parental consent. Adolescents were recruited through Facebook and Instagram advertising. In order to judge potential participants' capacity to consent, two multiple-choice questions about the consent process were required to be answered correctly prior to accessing the survey. This simple strategy effectively determined whether middle adolescents had the capacity to provide informed consent to participate in low risk online educational research.